2002
DOI: 10.1016/s1470-0328(02)01377-0
|View full text |Cite
|
Sign up to set email alerts
|

Secondary colposuspension: results of a prospective study from a tertiary referral centre

Abstract: Objective To evaluate the results of secondary colposuspension in women with recurrent urinary stress incontinence. Design Prospective cross sectional observational study.Setting Tertiary referral urogynaecology unit.Population Fifty-six women with recurrent stress incontinence.Main outcome measures Determine prognostic factors that may affect the outcome of surgery, long term subjective and objective success rates and identify complications of secondary colposuspension. Results The mean age was 54 years (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…However, urodynamic studies performed at time of post-operative review revealed a significant decrease in flow rate, which may reflect an element of outflow obstruction, although urinary residuals were low. These findings are in line with that of other authors [3,5,6,25,26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, urodynamic studies performed at time of post-operative review revealed a significant decrease in flow rate, which may reflect an element of outflow obstruction, although urinary residuals were low. These findings are in line with that of other authors [3,5,6,25,26].…”
Section: Discussionsupporting
confidence: 93%
“…We did not exclude patients with a low-pressure urethra and intrinsic urethral sphincter deficiency, which is thought to be an important factor in failure of continence surgery [22,23]. This could be a possible explanation for our low objective success rate compared with other reports in literature [3,5,6,12]. We measured an MUCP<20 mmH 2 O in 37.5% (n=6 of 16) of the women included in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…for Burch colposuspension after various index procedures, with objective cure rates of 81.1% (43/53 patients) . Two other studies on open colposuspension for failed continence procedures report objective and subjective cure rates to be 78–80 and 71–80%, respectively .…”
Section: Resultsmentioning
confidence: 97%
“…Seven studies on Burch colposuspension for recurrent SUI have reported in a total of 276 cases, with a 76% overall success rate (95% CI ±5.04) . According to Amaye‐Obu et al., who studied 26 patients, the Burch procedure had a cure rate of 81% (95% CI ±15.08) when it was carried out after one previous failed procedure (any procedure), 25% when it was done after two previous surgeries, and 0% after three previous procedures at a 2‐year follow up.…”
Section: Resultsmentioning
confidence: 99%